The Influence of Self-Control on The Intensity of Tiktok Usage Among Students of Muhammadiyah University Gresik - Ningrum, Fitria; Wicaksono, Awang Setiawan (World Psychology, 2025)
This study aims to examine the influence of self-control on the intensity of TikTok usage among students at Muhammadiyah University of Gresik. The phenomenon of increasing daily TikTok consumption among students has raised concerns regarding its potential impact on academic performance and social behavior. Using a quantitative approach with a correlational research design, data were collected from a sample of 120 students through validated self-control and TikTok usage intensity scales. The results of the statistical analysis using simple linear regression showed a significant negative correlation between self-control and TikTok usage intensity (p < 0.05), indicating that students with higher levels of self-control tend to spend less time on TikTok. These findings suggest that self-control plays a crucial role in regulating students' digital behavior, especially in managing social media usage. The study recommends that educational institutions implement self-regulation training and digital literacy programs to foster healthier media consumption habits among students.